The Efficacy of Psychological Interventions for Managing Fatigue in People With Multiple Sclerosis: A Systematic Review and Meta-Analysis - Phyo, Aung Zaw Zaw; Demaneuf, Thibaut; De Livera, Alysha M.; Jelinek, George A.; Brown, Chelsea R.; Marck, Claudia H.; Neate, Sandra L.; Taylor, Keryn L.; Mills, Taylor; O’Kearney, Emily; Karahalios, Amalia; Weiland, Tracey J. (Frontiers in Neurology, 2018)
Background: Multiple sclerosis (MS) is a complex, demyelinating disease of the central nervous system. Fatigue is commonly reported by people with MS. MS-related fatigue severely affects daily activities, employment, socioeconomic status, and quality of life. Objective: We conducted this systematic review and meta-analysis to determine whether psychological interventions are effective in managing fatigue in people with MS. Data Sources: We performed systematic searches of Medline, EMBASE, PsycINFO and CINAHL to identify relevant articles published from database inception to 5 April, 2017. Reference lists from relevant reviews were also searched. Study Selection and Design: Two independent reviewers screened the papers, extracted data, and appraised the included studies. A clinical psychologist verified whether interventions were psychological approaches. A narrative synthesis was conducted for all included studies. For relevant randomized controlled trials (RCTs) that reported sufficient information to determine standardized mean differences (SMDs) and 95% confidence intervals (CIs), meta-analyses were conducted using a random-effects model. Results: Of the 353 identified articles, 20 studies with 1249 people with MS were included in this systematic review. Narrative synthesis revealed that psychological interventions reduced fatigue in people with MS. Meta-analyses revealed that CBT decreased levels of fatigue compared to non-active controls (SMD = -0.32; 95%CI: -0.63 to -0.01) and compared to active controls (relaxation or psychotherapy) (SMD = -0.71; 95%CI: -1.05 to -0.37). Meta-analyses further showed that both relaxation (SMD = -0.90; 95%CI: -1.30 to -0.51), and mindfulness interventions (SMD = -0.62; 95%CI: -1.12 to -0.12), compared to non-active control, decreased fatigue levels. The estimates of heterogeneity for the four meta-analyses varied between none and moderate. Conclusion: This study found that the use of psychological interventions for MS-related fatigue management reduced fatigue in people with MS. While psychological interventions are generally considered first line therapy for MS-related fatigue, further studies are needed to explore the long term effect of this therapy.